Understanding Institutional Diversity - Ostrom, Elinor (Book collections on Project MUSE., 2005)
The analysis of how institutions are formed, how they operate and change, and how they influence behavior in society has become a major subject of inquiry in politics, sociology, and economics. A leader in applying game theory to the understanding of institutional analysis, Elinor Ostrom provides in this book a coherent method for undertaking the analysis of diverse economic, political, and social institutions. Understanding Institutional Diversity explains the Institutional Analysis and Development (IAD) framework, which enables a scholar to choose the most relevant level of interaction for a.